Re-emergence of social work in modern China: A perspective by Chinese and U.S. partners. Issue 1 (2nd January 2020) - Sherraden, Michael; Yuen-Tsang, Angelina Woon Ki; Wang, Sibin; Khinduka, Shanti; Zou, Li; Deng, Suo; Gao, Jianguo; Ku, Ben Hok-Bun; Huang, Jin; Sherraden, Margaret; Morrow-Howell, Nancy
ABSTRACT: In this article, we offer a perspective on the re-emergence of social work in China from the viewpoint of a longstanding and very productive partnership between Chinese and U.S. social work educators and researchers. We begin with a brief historical context, followed by a description of partnership development among Peking University, Hong Kong Polytechnic University, and Washington University in St. Louis. To illustrate academic collaborations and policy innovation in this partnership, we use asset building, productive ageing, and financial capability as examples. The partnership has also included joint efforts and interactions for social workers training in multiple forms. We conclude with some of the challenges and lessons in this partnership.